Pembelajaran Al-Qur’an Anti Radikalisme di Kalangan Pelajar Sekolah Menengah - Saputro, Fahmi Eko (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2020)
Radicalism is a problem of human civilization. Empirical facts show that high school-age children are very vulnerable to infecting radicalism. This is confirmed by surveys of research institutions that can be trusted. From this fact, schools / madrasas must start teaching that is able to ward off radicalism. Al-Qur'an subjects Hadith in Madrasas or Islamic religious education in secondary schools must be planned using the concept of learning anti-radicalism. One learning model that can be used is a scientific learning model. In the context of al-Qur'an material and hadith, students must be taught and introduced to study the Qur'an as a method of thinking. Thus, the understanding of the Qur'an and Hadith can be understood in its socio-historical context. Understanding related to asbab an-nuzul, makiyah-madaniyah and other analytical tools can be used so that the understanding of the Qur'an and non-intellectual traditions. This article seeks to prove that scientific learning can be used as a model of anti-radicalism learning. Learning the scientific model begins with observing, asking, gathering information, processing information, and communicating. With the steps of scientific learning in the material al-Qur'an and the hadith, allowing learning to be done by using theories of facilitation. Students can observe the cases that occur around them by observing news media online and also the understanding of the Qur'an and hadith from various sources. The information processing stage can be used so that the critical power of students towards the results of the interpretation of the Qur'an increases. Students can also discuss the results of gathering information obtained with their peers and the teacher becomes the facilitator. The conclusion that can be drawn in this study is that scientific learning can be used as a model of learning the Koran and the Hadith that has a spirit of anti-radicalism.